Frailty and quality of life after invasive management for non-ST elevation acute coronary syndrome. Issue 3 (14th May 2021) - Beska, Benjamin; Coakley, Daniel; MacGowan, Guy; Adams-Hall, Jennifer; Wilkinson, Chris; Kunadian, Vijay
Abstract : Objective: Older patients presenting with non-ST elevation acute coronary syndrome (NSTEACS) require holistic assessment. We carried out a longitudinal cohort study to investigate health-related quality of life (HRQoL) of older, frail adults with NSTEACS undergoing coronary angiography. Methods: 217 consecutive patients aged ≥65 years (mean age 80.9±4.0 years, 60.8% male) with NSTEACS referred for coronary angiography were recruited from two tertiary cardiac centres between November 2012 and December 2015. Frailty was assessed with the Fried Frailty Index; a score of 0 was characterised as robust, 1–2 prefrail and ≥3 frail. The Short Form Survey 36 (SF-36), an HRQoL tool consisting of eight domains spanning physical and mental health, was performed at baseline and 1 year. Results: 186 patients (85.7%) had invasive revascularisation. At baseline, 52 (23.9%) patients were frail and 121 (55.8%) were prefrail, with most SF-36 domains falling below the norm-population mean. Patients with frailty had lower mean scores in all physical SF-36 domains (p≤0.05) compared with those without frailty. Robust patients had temporal improvement in two domains (role physical +5.80 (95% CI 1.31 to 10.3) and role emotional +6.46 (95% CI 1.02 to 11.9)) versus patients with frailty and prefrailty, who had a collective improvement in a greater number of physical and psychological domains at 1 year (2 domains vs 11 domains), notably role physical (prefrail +6.53 (95% CI 3.85 to 9.20) and frail +10.4 (95% CI 6.7814.1)). Conclusions: Frail older adults with NSTEACS have poor HRQoL. One year following invasive management, there are modest improvements in HRQoL, most marked in frail and prefrail patients, who received a proportionally larger benefit than robust patients. Trial registration number: NCT01933581 .